2021
DOI: 10.3389/fnagi.2021.682115
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid of Patients With Alzheimer’s Disease Contains Increased Percentages of Synaptophysin-Bearing Microvesicles

Abstract: IntroductionIn Alzheimer’s disease, the severity of symptoms is linked to a loss of synaptic density and the spread of pathologically hyperphosphorylated tau. The established cerebrospinal fluid markers Aβ, tau and phospho-tau reflect the histopathological hallmarks of Alzheimer’s disease but do not indicate disease progression. Such markers are of special interest, especially for trials of disease modifying drugs. Microvesicles are produced by stressed cells and reflect part of the metabolism of their cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
0
6
2
Order By: Relevance
“…As amyloid-β accumulates, the severity of synaptic dysfunction intensifies, leading to tau hyperphosphorylation and the formation of tau tangles. Our study’s findings contradict J. Utz et al (2021), which showed increased synaptophysin levels in microvesicles isolated from cerebrospinal fluid (CSF) in AD [ 28 ]. This discrepancy could be due to different biofluid sources, cellular origins, or clearance mechanisms for synaptophysin in these compartments.…”
Section: Discussioncontrasting
confidence: 99%
“…As amyloid-β accumulates, the severity of synaptic dysfunction intensifies, leading to tau hyperphosphorylation and the formation of tau tangles. Our study’s findings contradict J. Utz et al (2021), which showed increased synaptophysin levels in microvesicles isolated from cerebrospinal fluid (CSF) in AD [ 28 ]. This discrepancy could be due to different biofluid sources, cellular origins, or clearance mechanisms for synaptophysin in these compartments.…”
Section: Discussioncontrasting
confidence: 99%
“…GPC has been shown to exhibit a favorable action in experimental models of the aging brain as well as in a rat model of pilocarpine-induced seizure ( 29 , 30 ), and to promote neuronal differentiation in a rat model of noise-restraint stress ( 29 ). In vitro assays performed in the SH-SY5Y human cell line have revealed that this cholinergic compound antagonizes neurotoxicity triggered by the fragment Aβ ( 25 35 ) of the Alzheimer’s amyloid β-peptide and attenuates the Aβ-induced phosphorylation of the Tau protein ( 31 ), by sustaining the expression level of synaptic vesicle proteins, such as synaptophysin ( 32 34 ). GPC was also shown to increase hippocampal neurogenesis, providing protection against seizure-induced neuronal death and cognitive impairment ( 26 ) and to antagonize scopolamine-induced amnesia enhancing hippocampal cholinergic transmission, suggesting that the behavioral effects of GPC could be related to its property to increase hippocampal synthesis and release of ACh ( 35 – 38 ).…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…The abnormal expression of synaptophysin has been associated with several brain disorders ( de Wilde et al, 2016 ; Osimo et al, 2019 ). For example, patients with AD have been found to have higher rates of synaptophysin-bearing microvesicles in their cerebrospinal fluid ( Utz et al, 2021 ). Moreover, synaptophysin has been suggested as a reliable marker of axonal damage in the CNS in demyelinating and neuroinflammatory conditions ( Gudi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%